A trinidadian cardiovascular medication adherence survey: the ADHERE TNT study - Seecheran, Naveen; Nandlal, Neval; Nankissoon, Sushanta; Nancoo, Cherisse; Nelson, Caniecea; Nkemakolam, Austell; Noel, Nadine; Olivers, Kwame; Parasram, Ryan; Rodriguez, Mario; Seecheran, Rajeev; Seecheran, Valmiki; et al. (International Journal Of Community Medicine And Public Health, 2017)
Background: This study aims to quantitatively estimate the level of cardiovascular medication adherence in Trinidad’s public health sector and to determine any correlating factors. The study was of a descriptive, cross-sectional design which was performed at a cardiology outpatient clinic located at a northern-central public health care tertiary hospital in Trinidad during the period November 2016 to June 2017. Methods: 595 persons in total were asked to participate, of whom, 535 agreed. Patients that were younger under the age of 18 years and those that declined participation were excluded from the study. Primary endpoints were the percentages of low, medium and high cardiovascular medication adherence. Secondary endpoints were the comorbidity prevalence rates and prevalence of cardiovascular medications prescribed to patients. Results: In total, 595 individuals were asked to participate in the study; of whom, 535 agreed with a resultant 90% response rate. The mean age of the sample population was 63.5 years. Approximately half of the respondents were females and over 75% had only primary and secondary level of education combined as well as a monthly income of <$5,000 Trinidad and Tobago dollars (TTD). Almost 75% of study participants had low and medium adherence levels, and conversely a little more than one-quarter had high adherence levels. There were no significant associations between adherence and any other demographic factor, however there was near-significance with respect to adherence and level of education (p= 0.061). Conclusions: Patients generally displayed a limited level of cardiovascular medication adherence which is likely to translate into a higher rate of cardiovascular events with their potentially devastating sequalae. This study underscores the imperative need of implementing comprehensive interventions to accentuate cardiovascular medication adherence in Trinidad and Tobago. Further comparable studies with reference national data are required to validate these findings.